Hepatic immune microenvironment dynamics in severe obesity and post-bariatric surgery: insights from immunohistochemical analysis - Alina-Iuliana Onoiu; Sergio González-Serrano; Vicente Cambra-Cortés; Andrea Jiménez-Franco; Carmen Guilarte; Karla Beatriz Peña; Francesc Riu; Jordi Camps; Jorge Joven; David Parada (Frontiers in Immunology, 2026)
Severe obesity is linked to metabolic dysfunction-associated steatotic liver disease (MASLD), which can progress to metabolic dysfunction-associated steatohepatitis (MASH) and advanced fibrosis. Currently, there are no accurate tissue biomarkers for measuring immune-mediated liver injury or remission post-bariatric surgery. This study utilized digital pathology and immunohistochemistry to analyze liver biopsies from three patient groups: those with severe obesity and liver damage before bariatric surgery, their paired re-do biopsies post-surgery, and patients with severe obesity and without evaluable liver injury per NASH CRN criteria. Quantitative metrics assessed immune cell proportions and staining areas from whole-slide images. Following bariatric surgery, patients experienced a significant reduction in body mass index (BMI) and improvements in liver histology, although lobular inflammation persisted at a median follow-up of six years. Analysis of the innate immune response showed a notable increase in CD15 + neutrophils postoperatively, along with a progressive accumulation of CD56 + natural killer cells across healthy and pre- and post-surgical cohorts. Additionally, long-term post-surgical samples exhibited higher densities of CD68 + and CD163 + macrophages. Within the adaptive immune compartment, the number of CD4 + T cells significantly increased after surgery, while the abundance of CD8 + T cells remained stable across all groups. Overall, the livers of postsurgical patients displayed the highest burden of immune cells and a restructured hierarchy of immune populations. This indicates the presence of a unique immune microenvironment associated with surgery rather than a return to a “healthy liver” profile. Despite metabolic and histological improvements post-surgery, persistent immune activation suggests a unique immunological state where immune cells may play dual roles in both liver damage and repair, emphasizing the need for comprehensive immune profiling and targeted therapeutic strategies.